Clinical recommendations in the management of the patient with type 1 diabetes on insulin pump therapy in the perioperative period: a primer for the anaesthetist. (January 2016) - Partridge, H.; Perkins, B.; Mathieu, S.; Nicholls, A.; Adeniji, K.
Abstract: Insulin pump therapy is increasingly common in patients with type 1 diabetes. Many of these patients will require surgery at some point in their lifetime. Few doctors will have experience of managing these patients, and little evidence exists to assist in the development of guidelines for patients with insulin pump therapy, undergoing surgery. It is clear that during emergency surgery insulin pump therapy is not appropriate and should be discontinued, but patients undergoing some elective surgery can and should continue insulin pump therapy, without any adverse effect on their blood sugar control, or on the outcome of their surgery. Individual hospitals need to formalize guidance on the management of patients receiving continuous subcutaneous insulin therapy, to allow patients the choice to continue their therapy during surgery. This expert opinion presents anaesthetists with a suggested clinical framework to help facilitate continued insulin pump therapy, during elective surgery and into the postoperative period.